Agency of Republic of Kazakhstan on Statistics : Statistical Master Plan 2008-2015 - World Bank (Washington, DC, 2013)
The mission of the Agency of the Republic of Kazakhstan on Statistics (ARKS) is to provide the Kazakh government, businesses and individuals with reliable and accurate statistics collected and produced in line with the international methodology and best practice. A Statistical Master Plan (SMP) is the internationally accepted, standard starting point for comprehensive improvement activities. With the participation of data providers, users, other national stakeholders and international donors, the ARKS has produced this SMP for the period up to 2015. The SMP builds upon existing national strategies and capabilities. It establishes and prioritizes data needs and sources. The SMP has two objectives: (1) present a strategy for the Kazakh National Statistical System (KNSS) development over the period to 2008-2015 and how it can be implemented; (2) provide a baseline assessment of the KNSS as the basis for strategy formulation. The SMP provides the basis and justification for investments by the ARKS and other government statistical agencies in improvements to the statistical infrastructure and program. It includes information that is vital to senior managers in preparing budget requests. The SMP was prepared by the ARKS with the assistance of a team of international experts funded by the World Bank who worked in conjunction with ARKS senior management and other stakeholders. The preparation process involved intensive consultation and input from the full range of stakeholders. In addition it benefited from close cooperation from a concurrent KNSS Global Assessment by a UNECE Study Group.